The Relationship Between Flatfoot and Static Balance in School-Aged Children - Mulyoto, Raufina Riandhani; Jannah, Suci Muqodimatul; Supinganto, Agus (Universitas Muhammadiyah Surakarta, 2022)
Introduction: Flatfoot is one of musculoskeletal deformities in the foot that is commonly seen in children. Previous study found that children with flatfoot have balance differences during standing as well as fatigue compared with children with normal feet that are associated with falling. Therefore, the purpose of this study was to investigate the correlation between flatfoot and static balance in children with flatfoot.Method: This was a cross sectional study design with purposive sampling data. The total sample was 16. Children were assessed using Chippaux-Smirak Index (CSI). The one-legged stance balance was used to assess static balance. Spearman correlation was conducted to examine the relationship between flatfoot and static balance in children.Results: The mean age of the participants was 7.94 years old in which they tend to have a second degree of flatfoot. There were significant differences in static balance between eyes open and eyes close in which the subject can maintain their balance longer while eyes open. However, there was no correlation between flatfoot and static balance in children.Conclusion: Flatfoot in school-aged children affects the balance performance where visual input plays an important role, even though there was no correlation between flatfoot and balance ability.